2012
DOI: 10.3389/fnins.2012.00118
|View full text |Cite
|
Sign up to set email alerts
|

The Decision to Fight or Flee – Insights into Underlying Mechanism in Crickets

Abstract: Ritualized fighting between conspecifics is an inherently dangerous behavioral strategy, optimized to secure limited resources at minimal cost and risk. To be adaptive, potential rewards, and costs of aggression must be assessed to decide when it would be more opportune to fight or flee. We summarize insights into the proximate mechanisms underlying this decision-making process in field crickets. As in other animals, cricket aggression is enhanced dramatically by motor activity, winning, and the possession of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 96 publications
(167 reference statements)
1
37
0
Order By: Relevance
“…Results demonstrated that the enhanced fighting performance of both winner and loser males was influenced by merely experiencing a previous contest, regardless of the outcome or even the occurrence of physical contact in previous contests. In the olive fruit fly, the experience of winning without physical combat evoked a behavioural effect similar to that detected in crickets, as in both species this experience alone is sufficient to enhance aggression and prolong fight duration in subsequent male-male contests 10 . This has an interesting parallel in humans, as it has been demonstrated that watching a previous victory raises the level of the aggression-promoting hormone testosterone 59 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Results demonstrated that the enhanced fighting performance of both winner and loser males was influenced by merely experiencing a previous contest, regardless of the outcome or even the occurrence of physical contact in previous contests. In the olive fruit fly, the experience of winning without physical combat evoked a behavioural effect similar to that detected in crickets, as in both species this experience alone is sufficient to enhance aggression and prolong fight duration in subsequent male-male contests 10 . This has an interesting parallel in humans, as it has been demonstrated that watching a previous victory raises the level of the aggression-promoting hormone testosterone 59 .…”
Section: Discussionmentioning
confidence: 97%
“…Aggressive behaviour can be severe between individuals of the same species, as they compete for the same food, territory, and access to mates 6 . Game theory predicts that Evolutionarily Stable Strategies for conflicts between conspecifics may involve stereotyped contests characterized by the ritualised exchange of agonistic signals 7 , which are thought to convey increasingly accurate information for assessing the contenders' chances of winning [8][9][10][11] . Probability of winning can depend on physical disparities (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Game theory predicts that evolutionarily stable strategies for conflicts occurring between conspecifics, may involve stereotyped contests featured by the ritualized exchange of agonistic cues 43, 44 . In this study, we investigated biomimetic aggressive interactions involving the Siamese fighting fish, Betta splendens (Regan) (Perciformes: Osphronemidae), and a conspecific-mimicking robotic fish in an open-loop agonistic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies, for example, those on escape behavior, phonotaxis, aggression and associative learning, have relied on electrophysiological, pharmacological and neuroimaging methods (Hedwig, 2006;Matsumoto and Mizunami, 2002;Ogawa et al, 2006;2008;Stevenson and Rillich, 2012). In spite of the many studies into a broad repertoire of behavior, the molecular basis that underlies these traits is still unclear.…”
Section: Introductionmentioning
confidence: 99%